Marine fish diversity and habitat use along the western coast of the Black Sea - Viorel Dumitru Gavril; Viorel Dumitru Gavril; Viorel Dumitru Gavril (Frontiers in Marine Science, 2015)
Over the years the conditions of the Black Sea marine habitats have been modified due to anthropogenic impacts and climate change, and it is likely that the diversity of fish fauna changed as a result. This study provides new data regarding marine fish population diversity and habitat use along the western coast of the Black Sea. I recorded fish species and habitat data between 2011 and 2014 in two locations: Constanta, Romania and Shabla-Tyulenovo coast, Bulgaria, using fishing (only in Romania) and scuba visual transects (Romania and Bulgaria). During this period, we identified a number of 45 fish species, belonging to 14 orders and 30 families. Observations made while scuba diving were of great importance for this study, as 47% of the species were identified using this method. These species include Sciaena umbra, Salaria pavo, Coryphoblennius galerita, Callionymus pusillus, Aphia minuta, Ophidion rochei, Diplodus annularis, and Chelidonichthys lucerna. Five broad types of habitats were delimited for the species identified: pelagic, sandy bottoms, rocky bottoms, rocky habitats with Cystoseira sp. and man-made structures like breakwaters. Vertically, the delimitation was made above and below the 10 meter line based on due to the differences in temperature, light penetration and surface wave interference. I identified 34 species of fish in the Shabla-Tyulenovo area and 39 species in the Constanta area, of which 19 species preferred sandy bottoms, 21 rocky bottoms, 16 rocky habitats with Cystoseira sp., 19 man-made structures and 9 were pelagic. For 7 species habitat preferences could not be determined as a result of capture only by fishing. In conclusion, the scuba visual transects along with fishing methods provide a relevant image to the current state of the fish diversity along the western coast of the Black Sea.